Dialogic, but Monologic: Toxic Masculinity Meets #MeToo in Teddy Wayne’s Campus Novel Loner - Kowal, Ewa (Text Matters: A Journal of Literature, Theory and Culture, 2023)
Teddy Wayne’s 2016 Loner tells the story of a Harvard freshman’s sexual obsession with a fellow student, leading to stalking and attempted rape. On a deeper level, the campus novel can be interpreted as a critique of wider processes taking place in American academia and generally in the US: the mainstreaming of the so-called “woke” movement and the growing impact of “political correctness.” The novel also reflects on class inequality, privilege, gender politics, the ongoing crisis of white (heterosexual) masculinity, toxic masculinity, and online “incel culture.” The present paper will analyze the problematic “dialogic, but monologic” nature of the book’s unreliable narrative addressing the above problems. The paper’s goal will be to read Loner in light of the #MeToo movement as an illustration of the current stage of the now decades-long reckoning with rape culture, and with patriarchy.